The selective nature of innovator networks: From the nascent to the early growth phase of the organizational life cycle - Uwe Cantner; Tina Wolf (Friedrich Schiller University Jena, 2016)
Earlier studies have shown that entrepreneurs play a key role in shaping regional development. Innovator networks where these entrepreneurs are members of have been identified as one among many critical factors for their firms' success. This paper intents to go one step further and analyses in how far differing characteristics of these networks lead to different firm performances along the early stages of the organizational life cycle (nascent stage, emergent stage, early growth stage). A sample of 149 patenting (innovative) firms in Thuringia is analysed, using data from the commercial register and the German patent office. The results show that there is an inverted u-shaped relationship between the chances of a firm to survive and the connectivity of the network the firms are connected to but only in the later stage of the early organizational life cycle; while the structure of the ego-network never plays a role. A quite central position in the network shows-up to be unfavourable.
Keywords: L25; L26; O30; L14; 330; Innovation; Entrepreneurship; Networks; Inventor; Patents; Survival